Effect of Sustentaculum Screw Position on Outcomes of Intraarticular Calcaneal Fracture Treated with Screw Only Technique - Chongmuenwai, Adisorn (Journal of Southeast Asian Orthopaedics, 2021)
Background: Placement of sustentaculum screws is an important procedure in calcaneal fixation. Inaccurate position may decrease stability of the fixation. Purpose: The aims of this study are to evaluate the effect of sustentaculum screw position on the decrease of Bohler's angle and FAAM (Foot and Ankle Ability Measure) score. Materials and Methods: Retrospective review of patients who underwent operative fixation of calcaneus fracture using screw only technique through sinus tarsi approach between July 2017 to March 2020 in Maharat Nakhon Ratchasima hospital. Postoperative sustentaculum screw positions were assessed with 3D-CT scan. Position of screws were grouped into good fixation (screw placed on cortical area of sustentaculum tali) and poor fixation group (screw placed out of cortical area of sustentaculum tali). The postoperative and 6-month follow-up Bohler's angles were compared. The FAAM was used to evaluate the clinical outcome at 6 months. Results: 38 patients (7females and 31males) with mean age of 48±11.6 were reviewed. The age of patients, preoperative Bohler’s angles and type of fractures showed no significant difference between two groups of the sustentaculum screw position. Postoperative 3D-CT scan classified 13 cases into the good fixation and 25 cases into the poor fixation groups. The decrease of Bohler's angle and FAAM score at 6 months showed no statistically difference between two group (P > 0.05). Conclusions: Position of the sustentaculum screw do not show statistical difference of the decrease of Bohler’s angle and FAAM score in operative treatment of intraarticular calcaneal fracture using screws only technique.